Group Brief Intervention: effectiveness in motivation to change alcohol intake - Janaina Soares; Divane de Vargas
ABSTRACT Objective: To verify the effectiveness of the group brief intervention (GBI), performed by nurses in motivational stages to change the pattern of alcohol intake. Method: Randomized controlled trial with 3-month follow-up. The ruler of readiness for change was applied in 180 individuals with risk or harmful alcohol intake pattern in basic health unit. Only the experimental group (EG) was submitted to the intervention. Both groups (experimental and control [CG]) participated in the follow-up. Results: EG had a mean score before GBI=6.55 (SD=3.41) points (preparation). After GBI=8.00 (SD=2.88) points (action) and in the follow-up 7.92 (SD=3.06) points (action). CG presented a mean score before GBI=5.42 (SD=3.26) points (preparation); after GBI=6.67 (SD=3.05) points (preparation) and in the follow up had a mean score of 4.80 (SD=2.86) points (contemplation). There was a statistically significant difference between the two groups at the motivational stages (p≤ 0,03). Conclusion: It was evidenced that GBI was effective in increasing the motivation to change harmful alcohol intake.